MITIGATION OF PUNISHMENT AND CRIMINAL DEFENSES IN CRIMINAL LEGISLATION OF CANADA AND REPUBLIC OF UZBEKISTAN (COMPARATIVE ANALYSIS) (TSUL LEGAL REPORT, 2026)
The existing paper provides a comparative analysis of the criminal legislation of Canada and Uzbekistan in terms of consideration of the mitigation of punishment and criminal defenses. In detail, the present research provides an overall overview of the mitigation of sentence institute in accordance with the existing editions of the Criminal Code of Canada and the Criminal Code of the Republic of Uzbekistan, including the issues of determining the punishment for the criminal offences committed in a state of mental disorder, as well as insanity and diminished responsibility for incomplete offences and criminal complicity, including criminal defenses, institutions on the withdrawal (voluntary refusal) from the commission of an offence and innocent harm, etc. Pursuant to the results of the conducted analysis, similar and different sides of current criminal laws have been clarified. Decisions on the performed analysis and a final conclusion on the implementation of Canada’s some criminal law norms to the criminal law of the Republic of Uzbekistan have been provided.